PROFIL BIBIT SAPI BALI YANG TERSERTIFIKASI DI PUSAT PEMBIBITAN SAPI BALI UNGGUL (PPSBU) GEROKGAK KABUPATEN BULELENG - Suwiti, N. K.; Suartha, I. N.; Inggriati, N. W.T.; Besung, I. N.K.; Heryani, L.G. S.S.; Sriyani, N. L.P. (Buletin Udayana Mengabdi, 2022)
Gerokgak District, Buleleng Regency, Bali has been designated by the Directorate General of Livestock, Ministry of Agriculture as the Center for Superior Bali Cattle Breeding (PPSBU). The total population of cattle in Buleleng Regency is 121,000 heads, and 42,000 heads are in Gerokgak District. The average community raises 3-4 Bali cattle per family. The quality of the cattle is unknown, so it is necessary to carry out certification through the bali cattle seed and Lembaga Sertifikasi Produk (Ls-Pro), Directorate General of Livestock, Ministry of Agriculture. The activity began with measuring 50 bali cattle at the Gerokgak PPSBU, and grouped them into grades. Bali cattle, which are grade I, were subjected to a PCR test for Jembrana disease as a requirement for filing for certification. The results of the activity showed that 56% of bali cattle were grouped into grade I, 30% grade II and 14% grade III. Ten heads (20%) of bali cattle breeds at PPSBU Gerokgak were submitted for certification.